2019
DOI: 10.1158/1541-7786.mcr-18-0429
|View full text |Cite
|
Sign up to set email alerts
|

The FGFR1 V561M Gatekeeper Mutation Drives AZD4547 Resistance through STAT3 Activation and EMT

Abstract: FGFR1 has been implicated in numerous cancer types including squamous cell lung cancer, a subset of non-small cell lung cancer with a dismal 5-year survival rate. Smallmolecule inhibitors targeting FGFR1 are currently in clinical trials, with AZD4547 being one of the furthest along; however, the development of drug resistance is a major challenge for targeted therapies. A prevalent mechanism of drug resistance in kinases occurs through mutation of the gatekeeper residue, V561M in FGFR1; however, mechanisms und… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 61 publications
(75 reference statements)
1
35
0
Order By: Relevance
“…One common mechanism of resistance is generated by mutating the so-called gatekeeper residue of the kinase domain [101]. The gatekeeper mutation has been reported in various kinases, such as Bcr-Abl (T315I) [102], EGFR (T790M) [68], PDGFR (T674I) [103], FGFR1 (V561M) [104] and FGFR2 (V565I) [105]. The gatekeeper residue lies at the beginning of the hinge region and controls the accessibility of the hydrophobic pocket.…”
Section: Fgfr Gatekeeper Mutation and Drug Resistancementioning
confidence: 99%
“…One common mechanism of resistance is generated by mutating the so-called gatekeeper residue of the kinase domain [101]. The gatekeeper mutation has been reported in various kinases, such as Bcr-Abl (T315I) [102], EGFR (T790M) [68], PDGFR (T674I) [103], FGFR1 (V561M) [104] and FGFR2 (V565I) [105]. The gatekeeper residue lies at the beginning of the hinge region and controls the accessibility of the hydrophobic pocket.…”
Section: Fgfr Gatekeeper Mutation and Drug Resistancementioning
confidence: 99%
“…As mentioned above, FGFR1 as an attractive target demonstrated modest response [42]. Therefore, signaling paradigm co-alternation with FGFR1 or genes have been widely studied, such as the co-active receptor tyrosine kinases, the co-activation of MTOR pathway, et al [15,19,43,44]. We demonstrated the co-expression of FGFR1 and CCND1 in lung cancer.…”
Section: Discussionmentioning
confidence: 58%
“…BGJ398 and AZD4547 are selective inhibitors of FGFR 1-3 in phase Ib clinical trials [15,16]. However, the efficacy of these inhibitors are modest [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The latest study from a phaseⅠclinical trial suggested that rogaratinib, a novel kinase inhibitor of FGFR1-4, resulted in an encouraging antitumor activity, if screened by FGFR mRNA overexpressing cancers [11]. In addition, the mutation in FGFR1 V561M gatekeeper drives the FGFR TKI AZD4547 resistance in vitro [12]. However, very few or none studies examined FGFR1 mRNA expression and mutation with tissue samples from patients and assessed their values.…”
Section: Ivyspringmentioning
confidence: 99%